Brand Positioning:The Unbeatable Weapon in Present Marketing Scenario - Diwan, Saloni Pawan; Jain, M. K. (Indian Journal of Marketing, 2009)
Over the decades, the sea change in the attitudes and lifestyles of people provided various big ideas to marketers, which can be nurtured out of changing social needs, desires and values of the target customers. These innovative ideas resulted in reshaping the thinking of marketers by first identifying and understanding the needs and expectations of the target group and then to come up with suitable products. In the present scenario, the innovations are taking place rapidly but even the best demanded brands are not sure regarding their survival because the innovations are difficult to develop and easy to copy. So, the marketers are continuously seeking the distinct positions for their brands in the minds of customers and hence brand positioning has emerged as the most challenging job in today’s mature and overcrowded markets. It aims at imprinting a differentiated image of the brand in the minds of the prospective customers. According to Charles Mittelstadt, "Positioning refers to how you want your brand ’thought about’ in connections with the competitors in its product category. It needs to be specific to your brand aimed at specific target audience". A successful brand positioning strategy concentrates on finding out the strong position in customer’s mind and then sitting on it, which leads to gain the competitive advantage in the market. The marketing managers are constantly facing the dilemma to position and reposition the brands according to the changing perceptions, needs and desires of the customers. Therefore, in the light of this fact, in this present study, we tend to focus upon describing the various strategies to position brands accurately in the market. The objective of our study is twofold. Firstly, to contemplate the basic concept of positioning and secondly, to give a brief account of puzzles and advancements in positioning.